Changes of patient-reported outcomes and protein fingerprint biomarkers after exercise therapy for axial spondyloarthritis - Husakova, Marketa; Siebuhr, Anne Sofie; Pavelka, Karel; Spiritovic, Maja; Bay-Jensen, Anne-Christine; Levitova, Andrea (Clinical rheumatology, 2019)
The objective of this study was to investigate the patient-reported outcomes (PROs) and matrix metalloproteinase (MMP) derived extracellular matrix (ECM) biomarkers in non-radiographic (nr)-axial spondyloarthritis (axSpA) and radiographic (r)-axSpA after exercise intervention. Forty-six axSpA patients with stable disease and treatment underwent 24 weeks long exercise intervention. The clinical and laboratory assessments were performed at baseline and at follow-up. The PROs included evaluation of patient's global disease activity (PGDA), disease activity (DA7), pain (PAIN7) and fatigue during last week and quality of life questionnaires. ELISAs for MMP-degraded collagen type II, C-reactive protein (CRPM) and citrullinated vimentin were used. The data of 23 r-axSpA and 19 nr-axSpA were analysed. The PDGA was similar for nr-axSpA (35.2 ± 18.9) and r-axSpA (33.4 ± 22.3) at baseline, improved significantly after intervention (p < 0.01) and the change of PDGA was almost identical for nr-axSpA (- 10.0 ± 15.4) and r-axSpA (- 9.8 ± 11.9). Evaluations of DA7 and PAIN7 were significantly improved only in nr-axSpA (3.5 ± 2.3 and 34.7 ± 25.6 at baseline vs. 2.1 ± 1.9 and 21.0 ± 20.5, respectively, p < 0.01). The decline of DA7 and PAIN7 was more profound, but not significantly in nr-axSpA than in r-axSpA (- 1.4 ± 1.6 and - 13.7 ± 17.4 vs. - 0.5 ± 3.1 and - 3.7 ± 3.3, respectively). The quality of life was not changed. At baseline, increased levels of CRPM were found in r-axSpA (14.85 ± 4.10) compared to nr-axSpA (11.83 ± 3.20), p < 0.05, but all three biomarkers were not influenced by exercise therapy. We found that exercise therapy mainly in the nr-axSpA improves PROs, but not ECM turnover biomarkers. This indicates that exercise therapy is important for patients' health but does not affect ECM turnover.
Keywords: Spondylarthritis; extracellular matrix; C-Reactive Protein; exercise therapy; C-reaktivní protein; mužské pohlaví; peptidové mapování; Adult; Patient Reported Outcome Measures; Peptide Mapping; Matrix Metalloproteinases; axial spondyloarthritis; kvalita života; ženské pohlaví; matrix metalloproteinase; Humans; hodnocení výsledků péče pacientem; biologické markery; spondylartritida; terapie cvičením; Exercise Therapy; dospělí; Biomarkers; Female; Quality of Life; lidé; Male; matrixové metaloproteinasy